2014
DOI: 10.3233/ves-140520
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol consumption impairs vestibulo-ocular reflex function measured by the video head impulse test and dynamic visual acuity

Abstract: Ethanol affects many parts of the nervous system, from the periphery to higher cognitive functions. Due to the established effects of ethanol on vestibular and oculomotor function, we wished to examine its effect on two new tests of the vestibuloocular reflex (VOR): the video head impulse test (vHIT) and dynamic visual acuity (DVA). We tested eight healthy subjects with no history of vestibular disease after consumption of standardized drinks of 40% ethanol. We used a repeated measures design to track vestibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…The impairment of eye movements by EtOH has been previously described across the entire gamut of voluntary and reflexive human oculomotor behaviours: saccades (Vorstius et al 2008;Roche & King, 2010;Silva et al 2017), smooth pursuit (Lehtinen et al 1982;Blekher et al 1997;Fransson et al 2010), vergence (Miller et al 1986;Miller, 1991), eccentric fixation (Romano et al 2017), the vestibulo-ocular reflex (Takahashi et al 1989;Post et al 1994;Roth et al 2014) and optokinetic nystagmus (Mizoi et al 1969). Previous studies showed that steady-state, closed-loop pursuit gain during tracking of sinusoidal or step-ramp target motion was significantly decreased at levels ranging from 0.04 to 0.10% BAC (Fransson et al 2010;Roche & King, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…The impairment of eye movements by EtOH has been previously described across the entire gamut of voluntary and reflexive human oculomotor behaviours: saccades (Vorstius et al 2008;Roche & King, 2010;Silva et al 2017), smooth pursuit (Lehtinen et al 1982;Blekher et al 1997;Fransson et al 2010), vergence (Miller et al 1986;Miller, 1991), eccentric fixation (Romano et al 2017), the vestibulo-ocular reflex (Takahashi et al 1989;Post et al 1994;Roth et al 2014) and optokinetic nystagmus (Mizoi et al 1969). Previous studies showed that steady-state, closed-loop pursuit gain during tracking of sinusoidal or step-ramp target motion was significantly decreased at levels ranging from 0.04 to 0.10% BAC (Fransson et al 2010;Roche & King, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Current studies could show that e.g. even alcohol and drugs may influence the results [ 178 ], [ 179 ], [ 180 ]. Furthermore, it became obvious that the highly-frequent hVOR is early impaired by gentamicin.…”
Section: Modern Technical Examination Of the Vestibular Systemmentioning
confidence: 99%
“…They are the measure for the assessment. Regarding the evaluation of the findings, also ENT specific reporting has to take into account that for example alcohol and drugs may influence the result of modern diagnostics [ 178 ], [ 179 ], [ 180 ].…”
Section: Modern Diagnostics Of Vertigo In Ent-specific Reportingmentioning
confidence: 99%
“…Aktuelle Studien haben gezeigt, dass z. B. auch Alkohol und Medikamente das Ergebnis beeinflussen können [178][179][180]. Darüber hinaus zeigt sich, dass der hochfrequente hVOR durch Gentamicin frühzeitig beeinträchtigt wird.…”
Section: Der Videokopfimpulstest In Der Notfallambulanzunclassified
“…Bei der Bewertung der Befunde muss auch im Rahmen der HNO-Begutachtung berücksichtigt werden, dass z. B. Alkohol und Medikamente das Ergebnis moderner Diagnostik beeinflussen können [178][179][180].…”
Section: Moderne Diagnostik Von "Schwindel" In Der Hno-begutachtungunclassified